Documentary rescue of the popular traditions of the cantons of the central area of the province of Heredia - Esquivel Alfaro, Elbethia (2009)
This paper presents the results of the documentary rescue practiced in different popular demonstrations in the cantons of the central area of the Province of Heredia. The final graduation work consisted of three important axes: the memory, the multimedia that contains all the information collected and a database in which the user, in addition to knowing the bibliographic production on the subject of Hereditary popular traditions has been produced, would help you physically locate these publications. In order to achieve the proposed objectives, visits were made to the public and municipal libraries of the province, as well as interviews with different artistic personalities of the Heredian cantons, which gave access to different legends, anecdotes, stories, songs, music and history of the province of Heredia.